2014
DOI: 10.1302/0301-620x.96b6.33086
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage revision for the infected total knee replacement

Abstract: Peri-prosthetic infection is amongst the most common causes of failure following total knee replacement (TKR). In the presence of established infection, thorough joint debridement and removal of all components is necessary following which new components may be implanted. This can be performed in one or two stages; two-stage revision with placement of an interim antibiotic-loaded spacer is regarded by many to be the standard procedure for eradication of peri-prosthetic joint infection. We present our experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 25 publications
2
46
0
2
Order By: Relevance
“…Our results in terms of survivorship free from infection with the single-stage approach appear comparable to those offered by a systematic review of the results of septic TKA revision, which reported mean eradication rates of 90.6% for two-stage and 89.2% for one-stage surgery [32] as well as with other recent studies on the subject of one-stage exchange [36,39,40]. The higher eradication rate after the two-stage revision, especially in combination with a mobile spacer, was based on numerous publications with shortterm followup and/or a low number of study patients with an eradication rate of up to 100%.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results in terms of survivorship free from infection with the single-stage approach appear comparable to those offered by a systematic review of the results of septic TKA revision, which reported mean eradication rates of 90.6% for two-stage and 89.2% for one-stage surgery [32] as well as with other recent studies on the subject of one-stage exchange [36,39,40]. The higher eradication rate after the two-stage revision, especially in combination with a mobile spacer, was based on numerous publications with shortterm followup and/or a low number of study patients with an eradication rate of up to 100%.…”
Section: Discussionsupporting
confidence: 85%
“…Standardized diagnostic and therapeutic algorithms for one-stage exchange have been described to make multicenter studies possible with comparable cohorts [13]. Two-stage revision with mobile or static spacers requires at least two surgeries, a longer period of time with limited mobility in the interval, and more possibility for perioperative complications and morbidity [24,28,32,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes host factors such as the patients medical and immune status, local soft tissue factors and virulence of the microorganism (See Key Factors Box). 1,3,5,8,10,11 Key factors influencing outcome of treatment.…”
Section: Acute Infection With Sepsismentioning
confidence: 99%
“…7e9 A one stage revision arthroplasty has also become a standardized treatment for chronic PJI in some specialized European centres, and has some potential benefits over a two stage revision. 8,10,11 Treatment for the acutely infected knee replacement is broader and can vary from irrigation and debridement with exchange of modular parts, to revision arthroplasty. Acute infection can present to the Orthopaedic surgeon on-call who may not have sub-speciality training in knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%